2001
DOI: 10.1046/j.1365-2826.2001.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superior Cervical Ganglionectomy on 24‐h Variations in Hormone Secretion from the Anterior Hypophysis and in Hypothalamic Monoamine Turnover During the Preclinical Phase of Freund's Adjuvant Arthritis in Rats

Abstract: The effect of superior cervical ganglionectomy (SCGx) on 24-h rhythms of circulating adrenocorticotropic hormone (ACTH), growth hormone (GH), prolactin and luteinizing hormone (LH) and of hypothalamic noradrenaline content and dopamine and serotonin turnover, was assessed in rats 3 days after administering Freund's complete adjuvant. In sham-operated rats, Freund's adjuvant injection increased serum ACTH without affecting its diurnal rhythmicity. SCGx, performed 10 days earlier, suppressed 24-h rhythmicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Our results were compatible with significant effects of immunemediated inflammatory response on hormone secretory processes, which were partially sensitive to immunosuppression by cyclosporine [24][25][26]. These as well as other studies indicated that significant changes in 24-hour rhythms did occur during experimental arthritis in rats [27][28][29][30][31][32][33][34][35]. As a continuation of those experiments, we hereby describe the 24-hour changes in thymic and serum concentration of GH and ACTH and their correlation with thymic concentrations of glutamate, aspartate, taurine and GABA (as indexes of thymic metabolism) in young and old rats during the acute phase of adjuvant's arthritis.…”
Section: Introductionsupporting
confidence: 87%
“…Our results were compatible with significant effects of immunemediated inflammatory response on hormone secretory processes, which were partially sensitive to immunosuppression by cyclosporine [24][25][26]. These as well as other studies indicated that significant changes in 24-hour rhythms did occur during experimental arthritis in rats [27][28][29][30][31][32][33][34][35]. As a continuation of those experiments, we hereby describe the 24-hour changes in thymic and serum concentration of GH and ACTH and their correlation with thymic concentrations of glutamate, aspartate, taurine and GABA (as indexes of thymic metabolism) in young and old rats during the acute phase of adjuvant's arthritis.…”
Section: Introductionsupporting
confidence: 87%
“…However, this secretion pattern has not been clearly demonstrated in male rats. Although the data are not always consistent, some reports indicate that PRL release in rats is dependent on the time of day (Castrillon et al 2001;Esquifino et al 2004;Garcia-Bonacho et al 2000). In contrast, a study by O'Connor, Van Pelt et al (2000) that was performed using rats with indwelling catheters for blood collection (and thus presumably decreasing the potential for stress-induced effects on PRL from the blood collection) found no differences in PRL concentrations as a result of the time of blood collection.…”
Section: Prolactinmentioning
confidence: 94%
“…Therefore, the loss, or decrease, of these adrenergic signals to the pineal gland must affect the production of MT. In fact, superior cervical ganglionectomy in rats induces early changes in 24-h rhythms and in hypothalamic content of noradrenaline [32]. For years it has been considered that MT simply acted as a synchronizer of the sleep-wake rhythm.…”
Section: Discussionmentioning
confidence: 99%